Journal of astrophysics and astronomy - Indian Academy of Sciences (Bangalore : Indian Academy of Sciences, 1980)
Access available online from 2001-
Title from cover.
Keywords: Astrophysics -- Periodicals; Astronomy -- Periodicals; Astrofysica; Sterrenkunde